2015
DOI: 10.1093/biomet/asv039
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of the pairs bootstrap for lasso estimators

Abstract: We study the validity of the pairs bootstrap for lasso estimators in linear regression models with random covariates and heteroscedastic error terms. We show that the naive pairs bootstrap does not provide a valid method for approximating the distribution of the lasso estimator. To overcome this deficiency, we introduce a modified pairs bootstrap procedure and prove its consistency. Finally, we consider the adaptive lasso and show that the modified pairs bootstrap consistently estimates the distribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Thus, we only deal with homoscedastic noise, as does the modified Lasso bootstrap in Chatterjee and Lahiri (2011). For Lasso models with heteroscedastic noise, it is possible to use other bootstrap strategies such as Camponovo (2015) and Wagener and Dette (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we only deal with homoscedastic noise, as does the modified Lasso bootstrap in Chatterjee and Lahiri (2011). For Lasso models with heteroscedastic noise, it is possible to use other bootstrap strategies such as Camponovo (2015) and Wagener and Dette (2012).…”
Section: Discussionmentioning
confidence: 99%
“…settings; see, e.g., Chatterjee and Lahiri, , Minnier et al , Efron , and Camponovo . In this paper, we extend the bootstrap procedure introduced in Camponovo to more general time series models, and prove its (pointwise) consistency. In our analysis, we mainly consider settings where the dimension p of the unknown parameter of interest is fixed and the sample size n is large.…”
Section: Introductionmentioning
confidence: 86%
“…Each observation in the sample is considered as a row vector z i = ( x i 1 , …, x ip , y i ),which consists of p predictor values x ij and a single outcome value y i . A Lasso model can be fit to every bootstrap sample of N observations z i , yielding a set of Lasso coefficient estimates (Camponovo, 2014). F̂ ( β̂ j ) is defined as the distribution of β̂ j values from each of all possible bootstrap samples of size N .…”
Section: Approachmentioning
confidence: 99%
“…She found that: 1) residual and vector bootstrap SEs of Lasso coefficient estimates had similar degrees of bias in linear models; and 2) vector bootstrap CIs had superior coverage in linear and in logistic models. Camponovo (2014) used vector bootstrapping to generate simultaneous confidence regions in linear models with random predictors. He found poor coverage rates, and used an asymptotic argument to propose two modified vector bootstrapping procedures.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation